2016
DOI: 10.1002/acr.22774
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Complete Remission in Systemic Lupus Erythematosus Patients Over a 32‐Year Period

Abstract: Objective. Systemic lupus erythematosus (SLE) is characterized by an unpredictable and fluctuating course. Although various methods have been developed to measure disease activity, there is still a lack of consensus about the optimal criteria for SLE remission. The principal aim of our study was to identify the number of lupus patients achieving a complete remission (implying that for 3 years there were no clinical or serologic features and no treatment with steroids and immunosuppressive drugs) in a single co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
46
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(51 citation statements)
references
References 18 publications
1
46
0
2
Order By: Relevance
“…The task force discussed whether definitions of remission should distinguish patients who are serologically active from those who are serologically inactive, as the former are much more likely to experience subsequent flare 4 9. No consensus was reached on that statement and the task force suggested to test each of the clinical criteria with and without serology, in order to determine the usefulness of the latter and whether it adds to the construct validity of each definition.…”
Section: Resultsmentioning
confidence: 99%
“…The task force discussed whether definitions of remission should distinguish patients who are serologically active from those who are serologically inactive, as the former are much more likely to experience subsequent flare 4 9. No consensus was reached on that statement and the task force suggested to test each of the clinical criteria with and without serology, in order to determine the usefulness of the latter and whether it adds to the construct validity of each definition.…”
Section: Resultsmentioning
confidence: 99%
“…An Italian study reported that 7.1% of their 224 SLE patients achieved sustained remission for 5 years or more, which was defined as a SLEDAI score of 0 and the absence of immunosuppressive therapy except HCQ 10. More recently, a study from UK defined complete SLE remission as clinical inactivity (British Isles Lupus Assessment Group scores of C, D and E only), absence of laboratory evidence of serological activity (normal complement and negative anti-dsDNA) and being off treatment except the antimalarial drugs 12. Of 532 patients, 14.5% achieved complete remission for ≥3 years and 4.3% did so for ≥10 years.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, there are no reliable predictors of SLE prognosis and the majority of studies concerning SLE prognosis have been clinical reports. It has been demonstrated that glomerulonephritis, vasculitis and hematological abnormalities are independent risk factors for the absence of clinical remission in patients with SLE (4) and a recent study, demonstrated that renal and neurological involvement decreased the likelihood of remission and favorable prognosis (35). The results of the current study are partially consistent with those from these previous studies, as it was demonstrated that renal involvement is an independent risk factor and increased levels of TLR9 mRNA and C-reactive protein in the whole blood are risk factors for poor prognosis in patients with SLE.…”
Section: Discussionmentioning
confidence: 99%